Dendritic cells phenotype fitting under hypoxia or lipopolysaccharide; adenosine 5′‐triphosphate‐binding cassette transporters far beyond an efflux pump. (18th April 2013) - Lloberas, N.; Rama, I.; Llaudó, I.; Torras, J.; Cerezo, G.; Cassis, L.; Franquesa, M.; Merino, A.; Benitez‐Ribas, D.; Cruzado, J. M.; Herrero‐Fresneda, I.; Bestard, O.; et al.
Summary This study examines adenosine 5′‐triphosphate‐binding cassette (ABC) transporters as a potential therapeutic target in dendritic cell (DC) modulation under hypoxia and lipopolysaccharide (LPS). Functional capacity of dendritic cells (DCs) (mixed lymphocyte reaction: MLR) and maturation of iDCs were evaluated in the presence or absence of specific ABC‐transporter inhibitors. Monocyte‐derived DCs were cultured in the presence of interleukin (IL)‐4/granulocyte–macrophage colony‐stimulating factor (GM‐CSF). Their maturation under hypoxia or LPS conditions was evaluated by assessing the expression of maturation phenotypes using flow cytometry. The effect of ABC transporters on DC maturation was determined using specific inhibitors for multi‐drug resistance (MDR1) and multi‐drug resistance proteins (MRPs). Depending on their maturation status to elicit T cell alloresponses, the functional capacity of DCs was studied by MLR. Mature DCs showed higher P‐glycoprotein (Pgp) expression with confocal microscopy. Up‐regulation of maturation markers was observed in hypoxia and LPS‐DC, defining two different DC subpopulation profiles, plasmacytoid versus conventional‐like, respectively, and different cytokine release T helper type 2 (Th2) versus Th1, depending on the stimuli. Furthermore, hypoxia‐DCs induced more B lymphocyte proliferation than control‐iDC (56% versus 9%), while LPS‐DCs induced more CD8‐lymphocyte proliferation (67% versus 16%). ABC transporter‐inhibitors strongly abrogated DC maturation [half maximal inhibitory concentration (IC50): P‐glycoprotein inhibition using valspodar (PSC833) 5 μM, CAS 115104‐28‐4 (MK571) 50 μM and probenecid 2·5 μM], induced significantly less lymphocyte proliferation and reduced cytokine release compared with stimulated‐DCs without inhibitors. We conclude that diverse stimuli, hypoxia or LPS induce different profiles in the maturation and functionality of DC. Pgp appears to play a role in these DC events. Thus, ABC‐transporters emerge as potential targets in immunosuppressive therapies interfering with DCs maturation, thereby abrogating innate immune response when it is activated after ischaemia.